2014
DOI: 10.3402/gha.v7.24995
|View full text |Cite
|
Sign up to set email alerts
|

Partner testing, linkage to care, and HIV-free survival in a program to prevent parent-to-child transmission of HIV in the Highlands of Papua New Guinea

Abstract: BackgroundTo eliminate new pediatric HIV infections, interventions that facilitate adherence, including those that minimize stigma, enhance social support, and mitigate the influence of poverty, will likely be required in addition to combination antiretroviral therapy (ART). We examined the relationship between partner testing and infant outcome in a prevention of parent-to-child transmission of HIV program, which included a family-centered case management approach and a supportive environment for partner disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
2
12
0
2
Order By: Relevance
“…The findings are consistent with data from two prior studies, 19,20 however, lack of benefit reported with partner PMTCT engagement in Malawi is in conflict with the outcomes found in this research. 21 Further studies may be needed to validate the findings in diverse geographic and cultural settings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings are consistent with data from two prior studies, 19,20 however, lack of benefit reported with partner PMTCT engagement in Malawi is in conflict with the outcomes found in this research. 21 Further studies may be needed to validate the findings in diverse geographic and cultural settings.…”
Section: Discussionsupporting
confidence: 86%
“…19 In a study from Papua New Guinea, there were significantly higher risks of infant deaths, HIV infections, or loss to follow-up if women lacked a partner, or reported that their male partners had not been HIV tested or had an unknown HIV testing status. 20 However, subsequent research from Malawi failed to detect lower vertical transmission risks with male partner involvement in PMTCT services. 21 …”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of men as part of the PPTCT programme however has faced additional health system challenges due to the historic and entrenched focus on women with few formal or informal opportunities to involve fathers in what have traditionally been maternal centric services . Further to this, it is likely that HIV‐related stigma and high rates of intimate partner violence in PNG have resulted in women fearing to disclose their HIV status particularly to partners or families . However, there is no way that a woman in PNG will ever be able to maintain life‐long treatment for any condition if she has not disclosed her condition to her partner.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à categoria suporte social emocional, observaram-se como fontes a família, 12,14,15,24,25,[27][28][29] o companheiro, 10,22,26 os amigos 15,24,27 e a crença em Deus e a fé, 15,24,27 como estímulos para continuidade do tratamento. Fica explícito que as questões culturais e familiares influenciaram nas decisões em relação aos cuidados de saúde maternos e infantis.…”
Section: Fontes E As Repercussões Do Suporte Social Emocionalunclassified
“…10,15,22,[26][27] Em contrapartida, muitas mulheres não revelaram seu estado sorológico ao companheiro por medo de divórcio ou violência doméstica, relacionado à submissão ao homem por ser o provedor de recursos financeiros. 10,22,26 Em um estudo com 28 mulheres soropositivas, 14 reconheceram a importância da realização das consultas de pré-natal e do tratamento mas, pelo medo de revelarem seu estado sorológico para o companheiro, elas não aderiram totalmente às medidas de profilaxia. 26 Nesse sentido, estudo teve como objetivo, esclarecer por que algumas mulheres inscritas em PPTV, em Lilongwe, Malawi, não participaram totalmente das visitas de acompanhamento nos primeiros seis meses após o teste HIV positivo.…”
Section: Fontes E As Repercussões Do Suporte Social Emocionalunclassified